2011
DOI: 10.4137/nmi.s5862
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Spirulina Platensis as a Nutritional Supplement in Malnourished HIV-Infected Adults in Sub-Saharan Africa: A Randomised, Single-Blind Study

Abstract: Background:Malnutrition is a major global public health issue and its impact on communities and individuals is more dramatic in Sub-Saharan Africa, where it is compounded by widespread poverty and generalized high prevalence of human immunodeficiency virus (HIV). Therefore, malnutrition should be addressed through a multisectorial approach, and malnourished individuals should have access to nutritional rehabilitation molecules that are affordable, accessible, rich in nutrient and efficient. We thus assessed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 34 publications
3
43
0
2
Order By: Relevance
“…Four of these studies were RCTs: three comparing one type of food supplement against another type of food supplement 18,25,26 and one unpublished report comparing 12 months of nutrition counseling alone to 12 months of nutrition counseling plus six months of food support (300 g/d of fortified blended flour). 15 The results from these four trials were mixed.…”
Section: Resultsmentioning
confidence: 99%
“…Four of these studies were RCTs: three comparing one type of food supplement against another type of food supplement 18,25,26 and one unpublished report comparing 12 months of nutrition counseling alone to 12 months of nutrition counseling plus six months of food support (300 g/d of fortified blended flour). 15 The results from these four trials were mixed.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies on HIV and/or severe immune deficient patients showed an increase in body weight when supplemented with Spirulina as well as increased haemoglobin levels, which in turn reduced anaemia (Azabji-Kenfack et al, 2011a).…”
Section: Moejes and Moejes 297mentioning
confidence: 99%
“…The long term use of highly active antiretroviral therapy (HAART) can lead to insulin resistance, dyslipidemia as well as weight and fat changes (Azabji-Kenfack et al, 2011a). Although dietary supplements have proven successful in the treatment of insulin resistance, the WHO states that the cheap and easily available Spirulina could be highly beneficial as it has shown to better glycaemic control, lower cholesterol and reduce blood pressure in diabetics.…”
Section: Hiv and Microalgaementioning
confidence: 99%
“…NADPH oxidase overactivity in disorders had suggested that ample intakes of Spirulina may prevent and has therapeutic potential with respect to many vascular diseases (including atherogenesis, hypertension, and congestive heart failure), cancers, complications of diabetes, and a range of neurodegenerative, fibrotic, or inflammatory disorder. Oral administration of phycocyanin or of whole Spirulina has exerted central neuroprotective effects in rodent studies -an observation which strongly suggests that PCB can transit the blood-brain barrier [411][412][413][414][415][416][417][418][419][420][421][422][423][424][425][426][427][428][429][430].…”
Section: Nutrition and Ageing Nutrition And Ageing Nutrition And Ageimentioning
confidence: 99%